Chemical principles in the laboratory - Slowinski, E. J. Emil J. Slowinski; Wolsey, W. C. Wayne C. Wolsey; Rossi, Robert C., Robert C. Rossi (Australia: Brooks, 2012)
This is a lab handbook that gives students the tools they need to execute lab experiments and lab reports effectively. Evaluating the data students witness in the lab sessions is simple thanks to the manual's numerous Advance Study Assignments, which provide further practice with data processing through sample questions.
Includes appendix
Keywords: Chemistry -- Laboratory manuals